Mapping conservation conflicts by integrating social network analysis and Q methodology: A sea turtle case from Sri Lanka - Maheshwaran Govender; Meenakshi Poti; Thanne Walawwe Gedera Fathima Mafaziya Nijamdeen; Kodikara Arachchilage Sunanda Kodikara; Farid Dahdouh-Guebas; Jean Hugé (Scientific Reports)
Abstract Conservation conflicts pose major challenges to biodiversity conservation, and addressing related stakeholder conflicts is gaining importance in the contemporary conservation discourse. We present an innovative approach to investigate conservation conflicts by combining Social Network Analysis and Q methodology. The study focuses on human–human conflicts among sea turtle conservation, tourism, and governance stakeholders in Sri Lanka. Our integrated approach simultaneously maps the collaborative relationships and the conservation viewpoints among 39 national, provincial, and local sea turtle stakeholders along the southern coast of Sri Lanka. Social Network Analysis reveals the dynamics of willingness and non-willingness for collaboration between stakeholders. Q methodology identifies three distinct clusters of conservation viewpoints. Perception 1 prioritises an integrated ecosystem approach to protect sea turtle eggs and the nesting beaches with community participation. Perception 2 promotes ex-situ conservation through sea turtle hatcheries, highlighting the economic benefits of sea turtle tourism. Perception 3 criticises the governance characterising the limited intersectoral collaboration and poor monitoring of the privately owned hatcheries. Mapping the conservation viewpoints within the stakeholder network highlights multi-scale conservation conflicts rooted in diverse stakeholder preferences and needs. Managing these conflicts is important for inclusive and effective sea turtle conservation and tourism in Sri Lanka.